For girls only : making a case for single-sex schooling - Streitmatter, Janice, 1952- (State University of New York Press, 1999)
For Girls Only examines research and public policy regarding single-sex schooling, especially girls-only classes in public, coeducational schools. Since the passage of Title IX in 1972, which calls for equal access and participation regardless of gender, educators have attempted to address gender equity issues in schools. Current research on the progress of female students in U.S. public schools suggests that efforts have not sufficiently addressed concerns such as academic under-achievement in the areas of math and science, lower self-esteem from the advent of early adolescence, and vulnerability to sexual harassment.